'Prosperity beyond belief': The interaction between a potato crop boom, vulnerability and volcanic hazard in Central Java, Indonesia. Issue 1 (18th July 2019) - Griffin, Christina
Abstract : This article examines the interaction between conditions of vulnerability and a potato crop boom in Central Java's highlands. While partaking in agricultural endeavours on volcanic slopes can bring substantial economic rewards, the local benefits associated with these livelihood activities are often overlooked by disaster scholarship. Drawing on a period of fieldwork conducted in the Dieng Plateau, a region characterized by a series of craters that periodically erupt mud and poisonous gas, this article demonstrates how a potato crop boom has evolved despite, and in part because of, the underlying volcanic hazard. By integrating the sustainable livelihood and agrarian change literatures, the article concludes that the potato boom has provided significant economic opportunity, and through this, a means to reduce vulnerability. Yet, despite these economic gains, the agrarian shift described herein has also introduced new vulnerabilities as farmers have become dependent on a resource intensive crop. These findings demonstrate how theories of agrarian transformation can complement livelihood perspectives in disaster research, and provide greater detail into the local and regional processes that encourage people to often‐profitably farm hazardous land.